2017
DOI: 10.1111/inm.12306
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' attitudes towards the use of PRN psychotropic medications in acute and forensic mental health settings

Abstract: Many countries now have national mental health policies and guidelines to decrease or eliminate the use of seclusion and restraint yet the use of Pro Re Nata (PRN) medications has received less practice evaluation. This research aimed to identify mental health nurses' attitudes towards the use of PRN medications with mental health consumers. Participants were working in forensic mental health and non-forensic acute mental health settings. The "Attitudes towards PRN medication use survey" was used and data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(60 citation statements)
references
References 58 publications
4
56
0
Order By: Relevance
“…For example, in the forensic mental health setting, Barr et al . () identified that there is an ongoing reliance on medication as a treatment option to reduce aggression, which precludes other strategies such as de‐escalation through the use of effective communication. Furthermore, the use of restrictive practices can reduce the consumer's power and responsibility to self‐regulate hindering their mental health recovery (Kuivalainen et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in the forensic mental health setting, Barr et al . () identified that there is an ongoing reliance on medication as a treatment option to reduce aggression, which precludes other strategies such as de‐escalation through the use of effective communication. Furthermore, the use of restrictive practices can reduce the consumer's power and responsibility to self‐regulate hindering their mental health recovery (Kuivalainen et al .…”
Section: Discussionmentioning
confidence: 99%
“…More restrictive interventions, such as restraint and higher rates of sedative medication, are reported to be used more commonly with consumers who are perceived by health professionals as a high‐risk group for becoming aggressive (Barr et al . ; Maguire et al . ; McKenna et al .…”
Section: Introductionmentioning
confidence: 99%
“…The majority of participants in this study reported administering PRN medication following appropriate assessment of the patient however a number of participants also perceived there to be an inappropriate use of PRN medication at times. Overreliance on, and poor practices around the use of PRN medication have been reported in many studies (Baker et al, 2007;Barr et al, 2018) with the suggestion that in some instances, its use may benefit staff more than patients (Curtis, Baker, & Reid, 2007). Participants in this study perceived that PRN medication was sometimes used as a means to keep patients quiet and to maintain calm on the unit and were given in the absence of any needs assessment.…”
Section: Discussionmentioning
confidence: 83%
“…Recognising the move towards partnership and recovery approaches to care, Hemingway and Snowden (2012) identify the responsibility of the nurse to have the appropriate knowledge, skills and caring attributes to attend to medication management sufficiently while being inclusive of patient needs and preferences. Nurses remain the key decision makers in the administration of PRN medication so there is increasing responsibility on them to be transparent about their decision to administer the drug (Barr, Wynaden, & Heslop, 2018). However, the role of clinical decision-making underlying nurses' administration of PRN medications is underresearched (Winship, 2010) and there is no published research on how mental health nurses in Ireland make a decision about administering PRN medication and how this process might be improved to provide a better experience for the service user.…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of system-level standards of practice for PRN administration, impact assessment, and documentation can help to improve overall patient safety in care homes [52]. Accountability for the administration of PRN medications can be improved by educating nurses in terms of vigilance over indications, reasons for use, medication effects and side effects, regular checking of prescribed medications, and continuous monitoring so as to avoid high dose medication and polypharmacy to ensure efficacy and prevent harm [9,[60][61][62][63].…”
Section: Discussionmentioning
confidence: 99%